ЗАВИСИМОСТИ ИЗНОСОСТОЙКОСТИ ПРЯЖИ ИЗ СВМ ВОЛОКОН ОТ УГЛА САМОИСТИРАНИЯ ПО МЕТОДУ ПЕТЛИ - Турманов, И. (SCIENCE and SOCIETY, 2020)
The article presents the results of a study of the wear before breaking from a high-modulus synthetic fiber using the loop method. It is determined that by an increase of the abrasion angle, there is an increase in the number of abrasion cycles before rupture